Firm performance and trade with low-income countries: Evidence from China - Hans-Jörg Schmerer; Luhang Wang (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
Do firms in developing countries shift trade towards developed economies as a result of high economic growth? The matched customs-manufacturing firm data used in this study confront this hypothesized link with empirical evidence. Our analysis reveals a rising low-income country trade share around and after China's accession to the World Trade Organization. Based on this stylized fact, we analyze the link between firm characteristics and trade with low-income countries. We find evidence for sequential sorting into different export-modes according to firm-productivity: i) only the most productive firms export to low-income countries, ii) exporting to low-income countries is mostly coupled to exporting to high-income countries, and iii) firms that switch to export to markets with higher potential are younger than firms that switch to export to both high- and low-income markets. Moreover, we find that firms tend to start exporting through specialization on high-income markets before diversifying to both type of markets. – – Erhöht Wachstum in Entwicklungsländern Handel mit entwickelten Ökonomien? Diese Arbeit untersucht das Exportverhalten chinesischer Firmen hinsichtlich des Handels mit Industrie- und Entwicklungsländern. Als Datenbasis verwenden wir gematchte Firmendaten mit detaillierten Informationen über Exportzielländer. Unsere Daten umfassen Chinas Beitritt in die WTO. Über den gesamten Zeitraum unserer Analyse finden wir einen leichten Anstieg der relativen Bedeutung anderer Entwicklungsländer für chinesische Exporteure. Aufbauend auf diesen stilisierten Fakten zeigt unsere Analyse, dass nur die produktivsten Firmen in Entwicklungsländer exportieren. Zum Zeitpunkt des Eintritts in den Export spezialisieren sich Firmen eher auf den Handel mit entwickelten Ökonomien. Länder mit niedrigerem Marktpotential werden tendenziell eher zusätzlich zu entwickelten Ökonomien bedient.
Keywords: F1; F6; O1; 330; trade with low-income countries; productivity; Chinese firms; firm level data; finance constraints; sequential exporting